Scientific Perspectivesof the US Administration - G. G. Malinetsky; V. V. Ivanov (Мир новой экономики)
The article presents a systematic analysis of state of arts in the US science, its organization and development prospects. Particular attention is paid to challenges in the scientific and technical sphere, which the Donald Trump administration is faced with, as well as first steps in this area. The experience of the US science organization, its role in future design, in assessment and evaluation of large scientific and technical projects, in decision of national security issues that can be used and adopted in reform of the scientific and technical sphere of Russia is discussed in details.